Climate Change Disclosures Are Getting Hotter. Issue 5 (July 2016) - Harrast, Steven; Olsen, Lori
Abstract : Since the publication of climate change disclosure guidance by the Securities and Exchange Commission (SEC) in 2010, the number of 10‐K disclosures has seen more than a twofold increase. Climate change disclosures are disclosures of risk from severe weather events and pollution, although a company may also report opportunities arising from climate change. In general, companies reporting weather risks disclose the potential for property damage and/or temporary loss of business. Companies with significant greenhouse gas and other nuisance emissions disclose risks due to litigation and the cost of compliance with regulations imposed by governmental bodies. A few companies have disclosed opportunities arising from climate change including initiatives to develop plant‐based plastics and renewable energy sources. The article provides a portrait of compliance with an emerging area of corporate risk disclosure. © 2016 Wiley Periodicals, Inc.